A modified diametrical compression test technique (MDCTT) for mode II fracture toughness of iron powder compact - Alabi, A. A.; Mohd Tahir, Suraya; Zahari, Nur Ismarrubie; Mohamed Ariff, Azmah Hanim; Anuar, Mohd Shamsul (Elsevier, 2017)
A sound knowledge of the fracture properties of a powder metallurgy (PM) component is essential for a design engineer to predict or prevent sudden fracture failure. Though iron powder is the most used base material in the PM industries, only its tensile mode fracture toughness (KIC) has been documented. This lack of adequate data can be traced to the non-availability of suitable test technique. In this paper, we present a new test approach for determining the mode II (shear mode) fracture toughness (KIIC) of iron powder compact. This method is known as the modified diametrical compression test technique (MDCTT). The MDCTT combined the qualities of diametrical compression test specimen with the pure shear mode failure of a riveted lap joint. The fracture toughness of copper powder compacts was also studied to corroborate the results of this technique. A comparison of the ratios for both powder compacts with theoretical predictions made using the maximum tangential stress criterion show strong agreement. Hence, the MDCTT is a suitable technique for determination of the KIIC values for iron and other metallic powder compacts.